Co-worker support and affective commitment during a global crisis: evidence from an emerging economy - Isaac Delali Darke; Philip Opoku Mensah; Frank Asamoah Antwi; Phyllis Swanzy-Krah (Cogent Business & Management, 2024)
A pandemic causes several disruptions and difficulties in work processes and the lives of workers. Given that the agricultural -sector remains an integral sector to human existence and livelihood, it was important to examine ways of ensuring that employees in the agricultural sector remain satisfied and committed during the novel COVID-19 pandemic. Underpinned by the Social Exchange Theory, this study sought to empirically examine the extent to which instrumental and emotional co-worker support affect employee affective commitment via job satisfaction. Primary data was obtained from 250 employees of 8 agro-processing companies in Ghana. Structured self-administered questionnaires were utilised and SPSS v26 and AMOS v26 were used for the data analysis. The results showed that instrumental and emotional co-worker support were positively and significantly related to employee affective commitment. Job Satisfaction also mediated the relationships between instrumental and emotional co-worker support and affective commitment Drifting from previous studies which largely focused on employees' affective commitment in service-based organizations, this study provides insights from the manufacturing sector. Additionally, in the context of the COVID-19 pandemic, which significantly disrupted on-site job structures and interpersonal interactions, this study addresses how co-worker support in such circumstances affect employee job satisfaction and affective commitment.
Keywords: 650; Co-worker support; instrumental co-worker support; emotional co-worker support; job satisfaction; affective commitment